Implementation of Peer Tutoring in Hybrid Learning for Media Literacy Subject: Students' Perception - Irra Wahidiyati (ELITE JOURNAL, 2023)
ABSTRACT This research discussed the application of peer tutoring in hybrid learning in teaching Media Literacy courses at the Faculty of Tarbiya and Teacher Training UIN Prof. K. H. Saifuddin Zuhri Purwokerto. It is a descriptive quantitative study. One of the courses in semester 4 is media literacy and is implemented in a hybrid way. Lecturers apply peer tutoring in media literacy lectures because the material includes the application of Microsoft word, excel, PowerPoint, infographics, LMS, and social media in learning. It isn't easy to implement when the teaching-learning is done online via Google Meet or Zoom. This study uses an interview and questionnaire distributed to 4th-semester students to obtain information related to their perception of the application of this peer tutoring. The questionnaire results stated that peer tutoring was beneficial offline and online. It's just that when offline, students can immediately check whether their friends apply what they are taught. If it is done offline, students can check each other's understanding by seeing their friends practice the material presented directly. At the same time, online, it will be challenging to check student understanding. When implemented online, students can only check the final result of what is taught that day, not the process. The advantages of implementing peer tutoring are to harness and further develop the skills of pupils who are already considered to be highly skilled in terms of providing friendship and support to others, to encourage the continued and ongoing use of 'support teams to ensure the inclusion of all students in the school context, to develop further the social and emotional skills of those students identified as members of the group. Keywords: hybrid learning, peer tutoring, perception